Minimization of transaction costs in the process of reproduction of national wealth - I. A. Gushchina (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2018)
The process of reproduction of national wealth is accompanied by transaction costs, which have a number of features. The structure of these costs is heterogeneous. Due to the fact that the bulk of the costs directly associated with the provision of exchange between individuals. Size and structure of transaction costs has a significant impact on the dynamics of investment in the development of the national wealth and its movement in stages of the reproductive process. Transaction costs create an incentive system that determines the behavior of individuals in certain circumstances. Due to the fact that the objectives of economic agents are mixed, then some of them will be interested in minimizing transaction costs and other directly will tend to increase. The problem of transaction costs in the process of reproduction of national wealth are unexplored in current economic literature. In this regard, it is expected to determine and clarify the nature of these costs, their causes, the distinctive features and characteristics. Clarified that the basic forms of transaction costs of reproduction of the national wealth are: the costs of finding the required resources and estimation of their useful properties; the opportunity costs; the costs of Contracting and enforcement; the costs of economic realization of ownership of human capital. The study of characteristics and forms of transaction costs, as well as the specifics of their manifestation enables minimization. To this end, developed evaluation criteria for all forms of transaction costs, explored the contradictory nature of the impact of transaction costs on the reproduction of the national wealth, institutional arrangements and tools, the use of which will allow not only to minimize these costs, but under certain conditions to ensure their growth..